Development of a quantitative and conformation-sensitive ATR-FTIR biosensor for Alzheimer's disease: The effect of deuteration on the detection of the Aβ peptide. Issue 1 (2010) - Kleiren Kleiren, Emilie Emilie; Ruysschaert Ruysschaert, Jean-Marie Jean-Marie; Goormaghtigh Goormaghtigh, Erik Erik; Raussens Raussens, Vincent Vincent
Abstract : Alzheimer's disease (AD) is the most common form of dementia worldwide and represents a growing socio-economical issue. To date, no reliable diagnosis can be obtained at an early-stage of the disease, though it is now recognized that the aggregation of the amyloid β (Aβ) peptide is responsible for the onset of the disease. Recent studies have shown that soluble amyloid oligomers present in the physiological fluids were the most neurotoxic species and correlated best with the first signs of cognitive decline, which makes them good biomarkers in the development of a diagnostic tool. We describe here a new type of biosensor, based on attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, that would be able to specifically detect and quantify the presence of the different forms of the Aβ peptide in solution. The principle of the detection relies on the recognition of the peptides by specific antibodies that were previously grafted on the surface of an ATR element, consisting of a functionalized germanium crystal. We show that the BIA-ATR technology is able to detect the presence of Aβ if incubated in deuterated water and that this step is crucial in the development of our conformation-sensitive biosensor for AD.